Evaluation of Brazilian ethanol production yeasts for maltose fermentation in media containing structurally complex nitrogen sources - Miranda Junior, M. [UNESP]; Oliveira, Jose Eduardo de [UNESP]; Batistote, M.; Ernandes, Jose Roberto [UNESP] (Inst Brewing, 2012)
Maltose and glucose fermentations are strongly affected by the structural complexity of the nitrogen source and by the presence of oxygen. In this study five industrial Saccharomyces cerevisiae strains were grown in synthetic medium, containing maltose or glucose, supplemented with different nitrogen sources, with or without agitation. All strains were able to grow and efficiently ferment glucose, but not all strains were able to grow and ferment maltose well. Peptone and ammonium sulfate induced improved fermentation for all strains and conditions. Under agitation, as expected, higher biomass accumulation was detected. Casamino acids supplementation induced efficient maltose fermentation for all of the strains under aerated conditions, but differing maltose utilization patterns were observed for the static cultures. Copyright (C) 2012 The Institute of Brewing & Distilling
Keywords: amino acids; ethanol production yeasts; maltose fermentation; nitrogen metabolism; oxygen; peptides; Saccharomyces; trehalose; yeast